Rat mesangial cells actively produce phosphatidy linositolanchored Thy-1 - Miyata, T. (1989)
We provide evidence that the mesangial cells of rat kidney glomeruli express Thy-1 as a phosphatidylinositol-anchored protein. Both the mesangial area of kidney, examined in tissue sections, and mesangial cells maintained in culture for more than 3 months, showed prominent immunofluorescence staining with an anti-Thy-1 monoclonal antibody (OX7); this staining was almost completely abolished by pretreating kidney sections or mesangial cells with the phosphatidy-linositol-specific enzyme, phospholipase C. By Northern blotting, mesangial cells were shown to express mRNA of an appropriate size, hybridizing to a mouse Thy-1.1-specific probe.